Stabilization Measure Adopted for Controlling Landslide: A Case Study of Upper Mai Hydroelectric Project - Chaulagai, Kanchan (Hydro Nepal: Journal of Water, Energy and Environment, 2017)
Stability is the key issue in landslide stabilization. Methodology and component adopted in stabilizing the slide play vital role in this regards. In many occasion, stability measure adopted for controlling slide has been found to be unsuccessful, inadequate causing not only the safety risk but also huge economic loss. This paper describe history, effects, causes, stabilization measures and effectiveness of these measures played for controlling landslide of headwork area of Upper Mai Hydroelectric Project. The pioneering solution applied for landslide stabilization such as application of rock bolts, shotcrete and water management found to be highly effective in controlling the landslide.  HYDRO Nepal JournalJournal of Water Energy and EnvironmentIssue: 21, July, 2017Page: 11-14Upload Date: July 18, 2017